Upaya Peningkatan Kemampuan Komunikasi Matematis Dan Kolaborasi Melalui Model Pembelajaran Problem Based Leraning (PBL) - Kurnia, Naafi Emma; Emma Kurnia, Naafi; Swastika, Annisa; Lestari, Sri (Program Studi Pendidikan Matematika, Universitas Islam Negeri Raden Fatah Palembang, 2024)
This classroom action research aims to improve students' collaborative attitudes and mathematical communication skills in learning mathematics by utilizing the Problem-Based Learning (PBL) model. Conducted in accordance with the Kemmis & McTaggart model, this study consisted of three cycles, with each cycle involving one lesson. The research subjects were eighth-grade students of SMP in Surakarta in the 2023/2024 academic year. Data collection was conducted using interviews, observations, and tests, which were analyzed descriptively. The results showed that the use of the PBL model succeeded in improving both the collaborative attitude and mathematical communication skills of the students. Therefore, it can be concluded that the application of the PBL learning model is effective in improving both aspects.